Magnetostructural phase transition assisted by temperature in Ag–αMnO2: a density functional theory study. Issue 10 (22nd February 2016) - Ochoa, Francisco Sánchez; Huang, Zhiwei; Tang, Xingfu; Cocoletzi, Gregorio Hernández; Springborg, Michael
Abstract : DFT and phonon calculations are performed to investigate the structural, stability, electronic and magnetic properties of atomic Ag chains hosted by MnO2 with a hollandite structure. Abstract : A crystalline material formed by parallel chains of silver atoms inside one-dimensional tunnels of hollandite manganese dioxide, Ag–αMnO2, is investigated through first-principles total energy calculations. Two different magnetic phases have been identified; one structure containing linear Ag chains with an antiferromagnetic ordering in the direction perpendicular to the MnO2 tunnels for T = 0 K ( I 4/ m ) and another configuration with zigzag Ag chains in a non-magnetic regime for higher temperatures ( P 21 / c ). According to phonon dispersions, both structures are stable. On the other hand, the structure with linear Ag chains in the non-magnetic state is unstable. A critical temperature of T c ≃ 125 K for the magnetostructural phase transition between the two stable structures I 4/ m and P 21 / c is predicted.